The Media and the image of war - Center for Defense Information (Washington, D.C.) (Washington, D.C.: The Center for Defense information, 1995)
Documentary on how'movies and television transmit from generation to generation a series of myths about war, peace, weaponry and the use of force
Video graphics, Adam Luther ; music, Ron Warren; director of television, Mark Sugg ; segment producer, Marguerite Arnold ; scriptwriter, Daniel M. Smith
Narrator, Kathryn Shultz
Keywords: Mass media and propaganda; Mass media and war -- United States